2018
DOI: 10.4491/eer.2018.043
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of dissolved organic matter in a constructed wetland: A molecular-level composition analysis using pyrolysis-gas chromatography mass spectrometry

Abstract: This study investigated the transformation of dissolved organic matter (DOM) in a free-water surface flow constructed wetland. Pyrolysis gas chromatography-mass spectrometry (Py-GC/MS) coupled with preparative high-performance liquid chromatography (prep-HPLC) was used to analyze the compositions of biopolymers (polysaccharides, amino sugars, proteins, polyhydroxy aromatics, lipids and lignin) in DOM according to the molecular size at three sampling points of the water flow: inflow, midflow, and outflow. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The relative abundance of these moieties can be related to two sources: (1) It is expected that following microbial activity, labile molecules will be favorably consumed, increasing the relative abundance of more complex recalcitrant compounds. In agreement with this general expectation, Park et al [47] showed an increase in aromaticity throughout a constructed wetland receiving secondary treated wastewater (shown for a free-water surface flow constructed wetland with a retention time of seven days). (2) Vegetation can serve as an important additional source of wetland organic matter, as in the RVFCW systems studied here.…”
Section: Discussionmentioning
confidence: 53%
“…The relative abundance of these moieties can be related to two sources: (1) It is expected that following microbial activity, labile molecules will be favorably consumed, increasing the relative abundance of more complex recalcitrant compounds. In agreement with this general expectation, Park et al [47] showed an increase in aromaticity throughout a constructed wetland receiving secondary treated wastewater (shown for a free-water surface flow constructed wetland with a retention time of seven days). (2) Vegetation can serve as an important additional source of wetland organic matter, as in the RVFCW systems studied here.…”
Section: Discussionmentioning
confidence: 53%
“…The specific ultraviolet absorbance at 254 nm (SUVA 254 , L.mgOC -1 .m -1 ), defined as the ratio of the absorbance at 254 nm to the organic carbon concentration was used as an indicator of the degree of aromaticity of the molecules [37,38]. Values of SUVA 254 above 4 and below 2 were considered to reveal highly aromatic and poorly aromatic molecules, respectively [31].…”
Section: Analyses Of Suspensions and Solutionsmentioning
confidence: 99%
“…The surface sludge layer is the siege of numerous reactions which induce the evolution of organic matter [26,28] that could in turn influence the quantity and the chemical nature of the DOM. Some studies have already monitored the concentration of DOM in VFCW systems, from inflow to outflow [29][30][31]. Kania et al [25] showed that SDs were sources of DOM and reported a pH-dependent leaching pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, terrestrial DOM, originating from plant litter and soil humus, contains mostly carbohydrates and lignin while autochthonous DOM, derived from algae and macrophyte, has a relatively high percentage of protein [8,9]. However, characteristics of DOM cannot be classified into two groups (terrestrial and autochthonous) because DOM is affected by various environmental factors such as source material, microbial community, and temperature [10][11][12].…”
Section: Introductionmentioning
confidence: 99%